Gene Expression Profile Reveals Abnormalities of Multiple Signaling Pathways in Mesenchymal Stem Cell Derived from Patients with Systemic Lupus Erythematosus. (27th August 2012) - Tang, Yu; Ma, Xiaolei; Zhang, Huayong; Gu, Zhifeng; Hou, Yayi; Gilkeson, Gary S.; Lu, Liwei; Zeng, Xiaofeng; Sun, Lingyun
Abstract : We aimed to compare bone-marrow-derived mesenchymal stem cells (BMMSCs) between systemic lupus erythematosus (SLE) and normal controls by means of cDNA microarray, immunohistochemistry, immunofluorescence, and immunoblotting. Our results showed there were a total of 1, 905 genes which were differentially expressed by BMMSCs derived from SLE patients, of which, 652 genes were upregulated and 1, 253 were downregulated. Gene ontology (GO) analysis showed that the majority of these genes were related to cell cycle and protein binding. Pathway analysis exhibited that differentially regulated signal pathways involved actin cytoskeleton, focal adhesion, tight junction, and TGF-β pathway. The high protein level of BMP-5 and low expression of Id-1 indicated that there might be dysregulation in BMP/TGF-β signaling pathway. The expression of Id-1 in SLE BMMSCs was reversely correlated with serum TNF-α levels. The protein level of cyclin E decreased in the cell cycling regulation pathway. Moreover, the MAPK signaling pathway was activated in BMMSCs from SLE patients via phosphorylation of ERK1/2 and SAPK/JNK. The actin distribution pattern of BMMSCs from SLE patients was also found disordered. Our results suggested that there were distinguished differences of BMMSCs between SLE patients and normal controls.